Influence of Glyphosate Timings on Conversion of Golf Course Rough from Tall Fescue to ‘Sharps Improved II’ Buffalograss - J. Reeves; J. Hoyle; D. Bremer; S. Keeley (Kansas Agricultural Experiment Station Research Reports, 2016)
All treatments, except the control that received no glyphosate application, resulted in acceptable buffalograss establishment (>90% buffalograss green cover) by 70 days after seeding (DAS). However, any treatment not sprayed prior to seeding date or that received a 7 DAS application lagged behind in establishment for 6 weeks after seeding.
Keywords: buffalograss; establishment; tall fescue; conversion